Investigation of in-vitro biological potential of Methanol extract of Magnolia alba Leaves - Sarah, Sabrina Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.